Analisis Faktor Persepsi Nasabah Bank Konvensional dan Switching Barriers Ke Bank Syariah - Slamet, Slamet; Munir, Misbahul; Hasan, Irmayanti (Fakultas Ekonomi, UIN Maliki Malang, 2019)
This research is to identify and analyze the factors of conventional bank customers' perception in Pondok Pesantren community in using Islamic banking services and identify and analyze switching barriers factors to become sharia bank customers for the Pondok Pesantren community. The paradigm in this research uses quantitative research with a CFA approach. The results showed that the factors that become conventional bank customers' perceptions in using Islamic banking for the Islamic boarding school community are comprised of three perceptions, namely customer perception variables consisting of a cognitive dimension, affective, and connectively. This means that respondents already have a dominant perception of the Islamic banking system. This is indicated byÂ that they have an understanding and knowledge of the existence and sharia banking system in Indonesia, although some of them use conventional banking services. There are several factors causing switching barriers to become customers of Islamic banks in the Pondok Pesantren community, from the loading factor value it is known that the dimension of value congruency is the dominant dimension in forming switching barriers variables in conventional banks.